2003
DOI: 10.1183/09031936.03.00292403
|View full text |Cite
|
Sign up to set email alerts
|

High Mallampati score and nasal obstruction are associated risk factors for obstructive sleep apnoea

Abstract: Induced nasal obstruction can cause obstructive apnoeas in healthy subjects during sleep, but the relationship between nasal resistance measured during wakefulness and obstructive sleep apnoea syndrome (OSAS) is weak. It was postulated that if the subjects could not breathe through the nose, the oral airway must be used, but if this airway is narrowed as well, then it could precipitate sleep-disordered breathing (SDB).Nasal patency, Mallampati score (MS), neck circumference and body mass index were measured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
88
1
12

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(105 citation statements)
references
References 19 publications
4
88
1
12
Order By: Relevance
“…By the same token, the association of SOAS and nasal obstruction has been broadly studied in the last two decades 18 . Udaka et al 19 showed, by means of a populational study with 4,818 patients, a positive correlation between nasal obstruction, daytime sleepiness and sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By the same token, the association of SOAS and nasal obstruction has been broadly studied in the last two decades 18 . Udaka et al 19 showed, by means of a populational study with 4,818 patients, a positive correlation between nasal obstruction, daytime sleepiness and sleep apnea.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with such conditions have two important obstruction points, increasing SOAS severity because the patient would put up a greater chest stress in order to overcome two levels of obstruction 18 . We observed that in a series of patients with High Mallampati score, that it is an important isolated risk factor for apnea appearance and worsening.…”
Section: Discussionmentioning
confidence: 99%
“…19 However, even without nasal obstruction, those with a Mallampati score of 3 or 4 have been reported to have a 1.95 relative risk of having OSAHS. 22 The Mallampati score could be easily carried out by dentists as part of a screening procedure, but in our study a high Mallampati score was not correlated to a diagnosis of OSAHS.…”
Section: Discussionmentioning
confidence: 66%
“…24,25 The use of the Mallampati score was based on the results of three studies of the use of this score as a clinical predictor for OSAHS. [19][20][21][22][23] Participants all had limited sleep studies (respiratory polysomnography) carried out using the Somnoscreen system (S-Med, UK) and manually analysed by a sleep technician (DM). The diagnosis of OSAHS was based on the daytime somnolence (an Epworth Sleepiness score ≥10) and an oxygen de-saturation index ≥10/hr).…”
Section: Methodsmentioning
confidence: 99%
“…Reported risk factors include obesity, increased neck circumference, male sex and anatomical abnormalities of the face [1,[8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%